A mini-review on high-entropy alloy nanomaterials for electrocatalysis: advances and prospects - Chen, Jiayu; Wu, Anni; Zhang, Yumin; Xie, Yongfeng; Zheng, Hu; Teng, Wei (Frontiers in Materials, 2025)
High-entropy alloy nanomaterials (HEA-NMs), composed of multiple metallic elements, offer tunable electronic structures, abundant active sites, and excellent stability, making them highly promising for electrocatalysis. This mini-review summarizes their structural effects influencing electrocatalytic behavior, recent advances in synthesis strategies, and electrocatalytic applications, including the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2RR), and nitrate reduction reaction (NO3RR). Challenges in synthesis scalability and mechanistic probing are discussed, along with future directions for atomic-level design and data-driven catalyst optimization. HEA-NMs offer a versatile platform for sustainable energy and environmental electrocatalysis.